Specific binding to plasma membrane is the first step in the uptake of non-transferrin iron by cultured cells - Musílková, J; Kriegerbecková, K; Krůsek, J; Kovár, J (Biochimica et biophysica acta, 1998)
We studied transport of non-transferrin iron into HeLa cells adapted for growth in defined medium, containing either 5 micrograms/ml of iron-saturated transferrin (HeLa/Tf cells) or 5 microM ferric citrate (HeLa/Fe5 cells) as a source of iron. Employing 55Fe-ferric citrate, iron uptake by intact cells was compared with iron binding to isolated membranes. Uptake characteristics of both HeLa/Tf and HeLa/Fe5 cells seemed to be similar: Km = 14 microM and Vmax = 135 pmol Fe/min/10(5) cells for HeLa/Tf, Km = 22 microM and Vmax = 165 pmol Fe/min/10(5) cells for HeLa/Fe5. Increasing concentrations (0.3-1.2 microM) of 55Fe-ferric citrate, producing levels of free 55Fe which were independent of total Fe under the experimental conditions used, led to increased binding of 55Fe for both HeLa/Tf and HeLa/Fe5 cells (1.08-8.03 nmol Fe/h/10(5) cells). This corresponds with the suggestion that iron was bound in the form of ferric citrate rather than in the form of free iron. Dissociation constants of Fe binding, KD = 0.61 microM for HeLa/Tf and KD = 1.53 microM for HeLa/Fe5, were obtained from competition experiments. We conclude that specific binding sites for ferric citrate are constitutively expressed in plasma membrane and that their expression does not require the induction by the presence of ferric citrate. The uptake of non-transferrin iron is realized in at least two steps. The first step is iron binding to the specific binding sites in plasma membrane. The binding does not represent a limiting step of the uptake.
Keywords: HeLa Cells; Biological Transport; Humans; železo; vazebná místa; Binding Sites; HeLa buňky; Cell Membrane; Iron; biologický transport; lidé; Clone Cells; buněčná membrána; transferin; buněčné klony; Transferrin